Progeroid Cockayne Syndrome - Anastasiya L. Kungurtseva; Alisa V. Vitebskaya (Вопросы современной педиатрии, 2024)
Cockayne syndrome is a rare genetic disease from the group of premature aging syndromes associated with impaired DNA repair. The syndrome is autosomal recessive, and it is caused by pathogenic variants in ERCC8, ERCC6, XPB (ERCC3), XPD (ERCC2), and XPG (ERCC5) genes. Its prevalence is 1 case per 2.5 million people. The clinical signs include nervous, cardiovascular and musculoskeletal systems impairments, severe growth retardation, and body weight deficiency. The average life expectancy of these patients varies from 5 to 30 years and depends on the disease type and severity. There is no pathogenetic treatment. This article presents the results of the latest research on the disease diagnosis and management.